Effect of Fish Bone Powder on Dough Rheological and Physicochemical and Microstructural Properties of Dried Instant KGM-Wheat Noodle - Sakamut, Phatthira; Wiangsamut , Thunwarat; Kerkchai , Somrudee (Science & Technology Asia, 2024)
Convenience foods include dried instant noodles, which are made from wheat flour and lack nutrients, especially calcium. This study made noodles by replacing 3-9% fish bone powder (FBP) for wheat flour. Increasing FBP decreased dough rheological characteristics, while replacing wheat flour with 9% FBP fluctuated considerably. In noodles, substituting FBP led to higher L*, a*, and b* values (p>0.05) and decreased tensile strength (p≤0.05), except in the 9% FBP sample. FBP lowered cooking times compared to wheat flour (p>0.05). All KGM-wheat noodles with FBP exhibited reduced water absorption (p≤0.05) and increased cooking loss (p≤0.05) compared to those without FBP. A sheet-like structure with local rupture and enlarged starch granules was found in the FBP substitution sample. KGM-wheat noodles replaced 3% FBP (calcium 754.42 mg), nearly meeting the 800 mg daily recommendation.